Analysis of fuzzy logic controller based bi-directional DC-DC converter for battery energy management in hybrid solar/wind micro grid system - M. Nagaiah; K. Chandra Sekhar (Institute of Advanced Engineering and Science, 2020)
This paper proposes a fuzzy logic-based battery energy management system in hybrid renewable system. The novel topology consists of solar and wind energy system-based input sources and a battery bank to store the energy when in excess. The PV-Wind source is equipped with unidirectional boost converter whereas, the battery storage system is connected to the system with a bi-directional DC/DC converter. The main novelty of this research is the fuzzy logic-based battery management system which charges and discharges into the DC bus system based on the supply-load demand. The fuzzy logic controller (FLC) based maximum power point tracking (MPPT) is used in the PV and wind energy conversion system (WECS) to track the maximum available power for the different irradiance and wind velocity respectively. The obtained results are compared to conventional P&O MPPT control algorithm to find the effectiveness of the system. A 500 W PV system and a 500 W Permanent magnet synchronous generator (PMSG) based WECS is implemented for its simplicity and high efficiency. The proposed control topology is designed and tested using MATLAB/Simulink